Comparative In Vitro and In Vivo Efficacies of Human Simulated Doses of Ceftazidime and Ceftazidime-Avibactam against Pseudomonas aeruginosa - Crandon, Jared L. (American Society for Microbiology, 2012)
The combination of ceftazidime and avibactam possesses potent activity against resistant Gram-negative pathogens, including Pseudomonas aeruginosa. We compared the efficacies of human simulated doses of ceftazidime and ceftazidime-avibactam using a hollow-fiber system and neutropenic and immunocompetent murine thigh infection models. Twenty-seven clinical P. aeruginosa isolates with ceftazidime MICs of 8 to 128 mg/liter and ceftazidime-avibactam MICs of 4 to 32 mg/liter were utilized in neutropenic mouse studies; 15 of the isolates were also evaluated in immunocompetent mice. Six isolates were studied in both the hollow-fiber system and the neutropenic mouse. In both systems, the free drug concentration-time profile seen in humans given 2 g of ceftazidime every 8 h (2-h infusion), with or without avibactam at 500 mg every 8 h (2-h infusion), was evaluated. In vivo activity was pharmacodynamically predictable based on the MIC. Ceftazidime decreased bacterial densities by ≥0.5 log unit for 10/27 isolates, while ceftazidime-avibactam did so for 22/27 isolates. In immunocompetent animals, enhancements in activity were seen for both drugs, with ceftazidime achieving reductions of ≥0.3 log unit for 10/15 isolates, whereas ceftazidime-avibactam did so against all 15 isolates. In vitro, ceftazidime resulted in regrowth by 24 h against all isolates, while ceftazidime-avibactam achieved stasis or better against 4/7 isolates. Mutants with elevated ceftazidime-avibactam MICs appeared after 24 h from 3/7 isolates studied in vitro; however, no resistant mutants were detected in vivo. Against this highly ceftazidime-nonsusceptible population of P. aeruginosa, treatment with human simulated doses of ceftazidime-avibactam resulted in pharmacodynamically predictable activity, particularly in vivo, against isolates with MICs of ≤16 mg/liter, and this represents a potential new option to combat these difficult-to-treat pathogens.